Analisis Alur Komunikasi Organisasi Pada Sub Divisi Account Receivable Officer PT Citra Baru Steel - Ferdiansyah Suroso Wongsokarto; Isma Yudi Primana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the flow of organizational communication in the Account Receivable Officer sub-division of PT Citra Baru Steel. Communication is a process of interaction between living things. Communication can be done by providing symbols, signals or through behavior and actions. Communication can be done verbally or non-verbally, verbally or in writing, with the aim being that the listener can understand the intention of the sender of the message. In (Saputro, 2018) Organizational communication, the process of conveying messages can take place formally from someone with higher authority to another person with lower authority, informally from someone with lower authority to someone with higher authority, horizontally from one person to another. who have the same authority, and across channels from those who occupy different functional part.